Laximicracis—a new genus of Afrotropical Micracidini beetles (Coleoptera, Scolytinae) - Jordal, Bjarte (Zootaxa, 2021)
During the revision of the micracidine genus Afromicracis Schedl, 1959, several species with unusual features required designation of a new genus. Features separating Laximicracis Jordal gen. nov. from Afromicracis includes a broadly rounded pronotum with small granules, an elongated and suture-free antennal club, a long tuft of setae on the female antennal scapus, a bispinate procurved apicolateral margin of the meso- and metatibiae, and long spatulate setae on tibiae and femurs. The new genus includes Laximicracis latipes Jordal, sp. nov. (Kenya), and the transfer from Afromicracis of Laximicracis dubia (Schedl, 1950) (Angola, Zambia, Tanzania) and Laximicracis convexus (Schedl, 1962) (South Africa). Collection localities are characterised by small dry forest patches and thickets, collected by UV- and white-light traps.